Cryoablation vs Radiofrequency Ablation in Atrial Fibrillation: Results of the latest trials - Ciechański, Erwin; Ciechański, Krystian Lech; Ciechańska, Magda (Journal of Education, Health and Sport, 2019)
In the recent years the importance of atrial fibrillation escalated rapidly. Despite having only 2% occurrence of total population in EU, becomes serious both medical and socioeconomical problem. According to the latest data one percent growth in the next ten years may be observed. There are many complications resulting from this disease such as: all cause deaths, brain strokes, heart failure and burden of health care caused by hospitalisations and lack of life quality. Pharmacological treatment of such disease is based on two strategies: antiarrhythmic drugs and cardioversions or ventricular rhythm control for permanent atrial fibrillation. Aiming at the specific group of patients with paroxysmal or persistent AF (atrial fibrillation) in both groups further invasive treatment should be considered. There are two main invasive treatments of AF – Radio frequency ablation (RF) and cryoballoon ablation (CRYO) as for the left atrium veins isolation. According to the The Cryo Vs RFA trial 208 patients underwent randomised clinical trial comparing CRYO, RF and COMBINED strategy. At 5 years of follow up, 57% of COMBINED patients remained free of AF after a single procedure compared to 47% CRYO and 19% RF patients. CRYO turned out to be superior to RF. Both of techniques combined had a significantly higher ratio of success in a single procedure efficacy. Aim of this study is to review newest trials comparing both of these techniques.